2013
DOI: 10.1021/ml400095m
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Series of Compounds with Potent Antiviral Activity for the Treatment of Enterovirus Infections

Abstract: Rhinovirus (genus enterovirus) infections are responsible for many of the severe exacerbations of asthma and chronic obstructive pulmonary disease. Other members of the genus can cause life-threatening acute neurological infections. There is currently no antiviral drug approved for the treatment of such infections. We have identified a series of potent, broad-spectrum antiviral compounds that inhibit the replication of the human rhinovirus, Coxsackie virus, poliovirus, and enterovirus-71. The mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…BF738735 was also active against HCV 1b with EC 50 ¼56 nM. MacLeod and colleagues reported that this compound was also based on a hit from high throughput screening [147]. Enviroxime itself was also proven to inhibit PI4K class III enzymes although with rather low selectivity [89].…”
Section: Inhibitors Of Pi4ks and Their Potential In Human Medicinementioning
confidence: 99%
“…BF738735 was also active against HCV 1b with EC 50 ¼56 nM. MacLeod and colleagues reported that this compound was also based on a hit from high throughput screening [147]. Enviroxime itself was also proven to inhibit PI4K class III enzymes although with rather low selectivity [89].…”
Section: Inhibitors Of Pi4ks and Their Potential In Human Medicinementioning
confidence: 99%
“…3,10,29,42 However, probes that replace the natural hydrophobic moiety, but do not compromise the infectivity and uncoating of the virus, could also act as potential markers and tools to study the function of the hydrophobic pocket. As far as we know, this is the first study to specifically label and visualize the pocket by using both gold nanoclusters and a fluorescent dye as visualizing tags.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vitro studies, acutely inhibiting PI4KIIIβ or PI4KIIIα kinases with small molecules such as PIK93, depleting them from the host cell, overexpressing kinase dead mutants or ectopically expressing phosphatases to lower PI4P levels, have all been shown to be successful in blocking viral RNA synthesis in many different types of infections [22,23,31,42,43], while not significantly affecting cell viability. The latter is likely due to compensation of host PI4P needs by redundant enzymatic activities provided by other, such as type II, PI4 kinase family members [28].…”
Section: Type III Pi4 Kinases As Panviral Therapeutic Targetsmentioning
confidence: 99%